Application The Farmer Business Using Method E-Market Place - Frengklin Matatula; Maura Widyaningsih (Journal of Telematics and Informatics, 2015)
Marketing of products from farmers so far has not been fully coordinated in the region specifically in Central Kalimantan. Although technology has developed, but for small and medium enterprises (SMEs) farmers are still untouched technology as a supporter of promotion and marketing products. Online-based marketing technology is a solution in terms of promotion and marketing. So product data in rural areas can be accessed easily, so it can reach every area . Application of vegetable growers based on digital using E_Market Place method, with the aim to facilitate the promotion and marketing of farmers' businesses online, so can be widely accessible. This matter to increase market sales of SMEs, in addition to the physical market that has been running among farmers. The application provides the availability of data and service management handling, if any changes or additions to sellers and products are promoted and traded online. Applications are supported by monitoring of buyers and revenue from each seller, so as to enhance the promotion and competitiveness of the products offered. Applications are also supported by shipping techniques that buyers can choose from, so that shipping and transaction costs can be known in advance from each purchase.